2009
DOI: 10.1111/j.1460-2466.2009.01454.x
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effect of Group Cue While Processing News on Immigration: Is the Framing Effect a Heuristic Process?

Abstract: This paper presents a study on the sociocognitive effects of news frames on immigration.One hundred and eighty-six individuals were exposed to a newspaper story on increased immigration to Spain. The newspaper highlighted (a) the positive (economic contribution frame) versus negative (crime growth frame) consequences and (b) the group cue-Latinos versus Moroccans. In contrast with economic contribution frame, crime growth frame stimulated more negative cognitive responses toward immigration, increased the sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
115
3
22

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(149 citation statements)
references
References 74 publications
9
115
3
22
Order By: Relevance
“…El análisis de los inmigrantes en los medios informativos ha sido un tema recurrente de estudio en los últimos años (Dixon y Linz, 2000;Entman, 1992;Igartua, Muñiz y Cheng, 2005;Igartua, Muñiz, Otero y de la Fuente, 2007;Romer, Jamieson y De Coteau, 1998;van Dijk, 1989). Las investigaciones que se han realizado sobre inmigración y minorías étnicas se han centrado en la cobertura y tratamiento informativo, señalando que son uno de los factores causantes del incremento de la xenofobia en el país (Igartua, Cheng, Moral, Fernández, Frutos, Gómez-Isla y Otero, 2008;Igartua y Cheng, 2009). La representación de la inmigración en los medios de comunicación, en especial en la prensa escrita y en los formatos informativos televisivos, ha sido un tema bastante estudiado por las Ciencias Sociales (Dixon y Linz, 2000;Entman, 1992;Igartua, Muñiz y Cheng, 2005;Igartua, Muñiz, Otero y de la Fuente, 2007;Igartua, Moral y Fernández, 2011;Muñiz, Otero, de la Fuente, 2013;Romer, Jamieson y De Coteau, 1998;van Dijk, 1989).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…El análisis de los inmigrantes en los medios informativos ha sido un tema recurrente de estudio en los últimos años (Dixon y Linz, 2000;Entman, 1992;Igartua, Muñiz y Cheng, 2005;Igartua, Muñiz, Otero y de la Fuente, 2007;Romer, Jamieson y De Coteau, 1998;van Dijk, 1989). Las investigaciones que se han realizado sobre inmigración y minorías étnicas se han centrado en la cobertura y tratamiento informativo, señalando que son uno de los factores causantes del incremento de la xenofobia en el país (Igartua, Cheng, Moral, Fernández, Frutos, Gómez-Isla y Otero, 2008;Igartua y Cheng, 2009). La representación de la inmigración en los medios de comunicación, en especial en la prensa escrita y en los formatos informativos televisivos, ha sido un tema bastante estudiado por las Ciencias Sociales (Dixon y Linz, 2000;Entman, 1992;Igartua, Muñiz y Cheng, 2005;Igartua, Muñiz, Otero y de la Fuente, 2007;Igartua, Moral y Fernández, 2011;Muñiz, Otero, de la Fuente, 2013;Romer, Jamieson y De Coteau, 1998;van Dijk, 1989).…”
Section: Introductionunclassified
“…En la segunda se mantiene una predilección por una variedad de "problemas" de los cuales son acusados los inmigrantes (culpabilización de la víctima), y finalmente, en la tercera los medios toman preferencia por un pequeño conjunto de temas negativos (planteando la inmigración como invasión, ataque o amenaza y asociándola a violencia, terrorismo y/o desintegración social) (Muñiz e Igartua, 2004). medios de comunicación-han señalado que estos influyen en la percepción, las actitudes y las creencias que sobre la inmigración hay en el país receptor (Brader, Valentino y Suhay, 2008;Domke, McCoy y Torres, 1999;Igartua y Cheng, 2009;Igartua, Moral y Fernández, 2011). Una de las principales consecuencias de este tratamiento informativo es la creación y/o mantenimiento de determinados estereotipos 6 y prejuicios sobre los inmigrantes.…”
Section: Introductionunclassified
“…In this context, Igartua and Cheng (2009) observed that the incidental inclusion of the nationality of immigrants (Moroccans in comparison to Latin Americans), in the context of a news story about the consequences of immigration for Spain, worsens prejudice and reinforces negative attitudes and beliefs towards inmigrants in general. These results converge with studies on the role of (textual and visual) cues on the ethnicity or nationality of the protagonists of the news stories in the activation of stereotypes (e.g., Gilliam, Iyengar, Simon and Wright, 1996;Peffley, Shields and Williams, 2001).…”
Section: Mechanisms Of Framing Effectsmentioning
confidence: 99%
“…with the activation of "trains of thought" that spontaneously influence the formation of attitudes and beliefs, thanks to the emphasis put on certain attributes in the news story (on-line model) Price, Tewksbury and Powers, 1997). A third position considers that the framing effect is linked to the processes of persuasion and, in this context, it has been proposed that this effect may be ruled by the heuristic processing (Igartua and Cheng, 2009;Igartua, Moral and Fernández, 2011;Perse, 2001;von Sikorski and Schierl, 2012). This means that the impact of news framing would be related to the activation of cognitive processes that do not involve a comprehensive analysis of information, i.e., with the activation of mental shortcuts and attitudinal modelling processes, so that the implicit attitude in the news is automatically assimilated, without causing a reflection or elaboration processes on individuals.…”
Section: Mechanisms Of Framing Effectsmentioning
confidence: 99%
See 1 more Smart Citation